Management of Adult Patients with Newly Diagnosed or Relapsed Primary Immune Thrombocytopenia in Eastern Austria - Rast, Jasmin; Schramm, Theresa; Mehic, Dino; Fillitz, Michael; Drexel, Tanja; Neusiedler-Nicolas, Veronika; Ay, Cihan; Pabinger, Ingrid; Gebhart, Johanna (Hämostaseologie, 2024)
Background Treatment sequence in primary immune thrombocytopenia (ITP) is based on national and international recommendations, treatment availability, and physician expertise.Aim This article aimed to provide real-world data on treatment sequence and responses to first- and second-line treatments in newly diagnosed and relapsed adult ITP patients.Methods We analyzed a cohort of 46 adult ITP patients from the Vienna ITP Biobank, who started first-line therapy within 1 week before their first study visit between February 2016 and March 2023. We investigated clinical patient characteristics and patient management in our specialized center and examined the impact of the international ASH guidelines on ITP treatment.Results Forty-six primary ITP patients, 27 (58.7%) with newly diagnosed ITP and 19 (41.3%) with relapsed ITP, were investigated. Most patients were female (65.2%) with a median platelet count of 9 × 109/L, and 31 patients (67.4%) had bleeding symptoms. All patients received first-line treatment with oral prednisolone; 15 patients received oral prednisolone combined with intravenous immunoglobulins (IVIGs), which were more commonly administered in newly diagnosed than in relapsed ITP patients. First-line therapy resulted an overall response in 82.6% of patients after a median (interquartile range [IQR]) time of 10 (5–25) days. There was no difference in treatment responses between newly diagnosed and relapsed ITP patients, but newly diagnosed patients had a shorter time to response (median [IQR]: 8 [5–14] and 14 [8–27], p = 0.02). Twenty-three (50%) of the patients (11/27 newly diagnosed [40.7%], 12/19 relapsed [63.2%]) required second-line ITP therapy. Thrombopoietin-receptor agonists (TPO-RAs) were the most commonly used second-line therapy with a response rate of 73.7%, and a median (IQR) time to treatment response of 15 (12–20) days. Overall response rates to TPO-RA treatment did not differ between newly diagnosed and relapsed ITP. Following the publication of novel guidelines in 2019, the median (IQR) duration of corticosteroid treatment shortened (100–52 days, p = 0.01), as did the time to second-line treatment (160–47 days, p = 0.01), and the median number of first-line therapies decreased from 2 (1–3) to 1 (1–2).Conclusion Initial treatment with corticosteroids was effective in the majority of newly diagnosed and relapsed ITP. Response rates to initial corticosteroid treatment in ITP patients are consistent with previous data, but only 50% achieve sustained remission. TPO-RAs, which are well tolerated and effective, are the most commonly used second-line therapy in our study population. International guidelines have led to faster treatment transitions and reduced splenectomy rates. Integration of real-life experience, expert consensus, and guidelines optimizes ITP patient management.
Keywords: primary immune thrombocytopenia; platelet function; bleeding severity; first-line therapy